KEKUASAAN EKSEKUTIF INDONESIA BERDASARKAN KONSTITUSI INDONESIA SAAT INI - Purnomowati, Reni Dwi (Ensiklopedia of Journal, 2024)
One important issue to arranged in constitution of state is executive power. The executive power is arranged in constitution, there are recruitment, duties, functions and authority. The research are discussed about constitutional law theories and implementation in Constitution of Indonesian 1945 now. The reasons discuss executive power issue, because presidential executive  system  characteristic have big implication in Indonesian politic system, and to answer the research questions are formulated by : First, How change direction executive power in Amendment of Constitution of Indonesian 1945?; Second, How executive power in Constitution of Indonesian 1945?; Third, How presidential executive system are arranged in Constitution of Indonesian 1945 now?. This research is normative research by document study, which research of law system. Conclusions of this research are : First, amendment of Constitution of Indonesian 1945 more confirm characteristic presidential executive and check and  balances system; Second, functions of executive powers, are diplomatic, administration, military ,judicative and legislative had arranged in Constitution of Indonesian 1945 now; Third, Constitution of Indonesian 1945 now had fulfilled a state with presidential executive system characteristic according to C.F. Strong, however still have parliamentary executive system characteristic in Article 7A Constitution of Indonesia, Amendment third. Keywords: Authority, Constitution, Duty, Executive, Presidential